Fostering The Learning Achievement of Students Xi Ipa4 at SMAN 3 Jember in Even Semester by using The Cooperative Method Of TGT Model on Functional Limit Material in 2018/2019 Academic Year - Teripena EC (Pancaran Pendidikan, 2019)
Mathematics refers to the material which has an abstract object and is built on deductive reasoning processes, covering the truth of a concept obtained as a logical consequence of previously accepted truths. To be easily understood by students, deductive reasoning processes on mathematics learning is used to strengthen the understanding that students already have. The purpose of learning mathematics is to train how to think systematically, logically, critically, creatively and consistently. This research was based on several problems: (a) What is the improvement of students’ learning achievement by implementing TGT cooperative learning method? (b) What is the effect of TGT cooperative learning method on students’ learning motivation?. While the objectives of this study were: (a) Finding out the increase in students’ learning achievement after the implementation of TGT cooperative learning method. (b) Knowing the effect of students’ learning motivation after TGT model of cooperative learning was applied. This research used action research as many as three cycles. Each cycle consisted of four stages, they were: design, activity and observation, reflection, and refining. The targets of this research were the students of class XI IPA4 at SMAN 3 Jember. The data obtained were in the form of formative test results, observation sheets of teaching and learning activities. It can be concluded that TGT model cooperative method had positive effect on the students' learning motivation in understanding the material concept of opportunities so that they were able to achieve maximum learning achievement and this learning model is also capable to be used as an alternative mathematics learning so that the teachers can convey mathematical material concepts and absorbed by the students more effectively.